Evolution of the spherical cell shape in bacteria : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Genetics at Massey University, Albany, New Zealand - Yulo, Paul Richard Jesena (Massey University, 2019)
Cell shape is an important feature of bacterial cells. It is involved in critical aspects of bacterial cell biology such as motility, growth, and the evasion of predators. Despite this, how cell shape has evolved in bacteria is unclear. For most rod-shaped bacteria, the maintenance of cell shape depends primarily on the bacterial actin-like protein, MreB. In this study, we show that the deletion of MreB from the rod-shaped model organism Pseudomonas fluorescens SBW25 results in the formation of aberrant spherical cells that have increased size and reduced fitness. This new MreB-null strain (ΔmreB) is susceptible to mechanical damage and grows poorly due to cell division defects. Furthermore, synthesized peptidoglycan (PG) chains were shorter and cell wall assembly was disorganised in this strain. A 1,000-generation evolution experiment comprised of multiple independent lineages produced spherical cells that have a reduced cell size and improved fitness. Mutations in the PG synthesis protein PBP1a were found across multiple lineages. Genetic reconstructions demonstrated that these mutations have a loss-of-function effect that reduced PG cross-linking and restored the ordered assembly of the cell wall, thereby reducing cell size and improving fitness in MreB-null cells. In one lineage, a five-gene deletion that included the gene coding for the outer membrane channel OprD was found to be beneficial. This deletion reduced cell size, improved fitness, and restored orderly cell wall construction. The mechanism responsible for this is unknown, but it may be related to modifications in septum localisation via the Min system. Finally, we show using phylogenetic analysis that PBP loss is a general trend in bacteria that evolved to become spherical, hinting at a plausible strategy for the evolution of the spherical cell shape from rod-shaped progenitors.
Keywords: Bacteria; Morphology; Evolution; Molecular microbiology; 310104 Cell neurochemistry